Shadow Animals how animals we fear can help us heal, transform, and awaken - Brunke, Dawn Baumann (Rochester, Vermont Bear & Company, 2022)
"A guide to shadow work with animal teachers"--
Introduction. The Cat, the Snake, and the Shadow -- Part 1. Opening to Our Shadow Teachers -- Part 2. Thirteen Shadow Guides.
Includes bibliographical references (pages 297-304) and index.
113238
Keywords: Animals -- Therapeutic use